(untitled) (Global Journal of Science Frontier Research, 2018)
Two pot experiments were carried out in the greenhouse of the National Research Centre, Dokki, Giza, Egypt, in the two successive summer seasons, 2015 and 2016 to study the allelopathic potentiality of garlic cloves water extracts (gcwe) on sunflower growth and yield as well as its effect on the growth of purple nutsedge associating garlic plants. Treatments were applied by the spraying of garlic cloves water extracts (gcwe) at 15. 30, 45 and 60 %. The results showed that sunflower growth and yield exhibited the most increase at lower concentrations of garlic cloves water extract. On the other hand, purple nutsedge growth showed complete inhibition with the high concentrations. The results suggested the use of garlic cloves water extract as an alternative to the use of herbicides for controlling purple nutsedge associating sunflower plants.